Thermal and entropy behavior of sustainable solar energy in water solar collectors due to non-Newtonian power-law hybrid nanofluids - Mabrouk, S. M.; Mahmoud, Tarek A.; Kabeel, A. E.; Rashed, A. S.; Essa, Fadl A. (Frontiers in Energy Research, 2023)
Nanotechnology and solar radiation make water solar collectors popular nowadays. Unlike other nanofluids, hybrid nanofluid possesses thermophysical features that boost the fluid performance. This research work is motivated by the utilization of water solar collectors that incorporate non-Newtonian, power-law hybrid nanofluid in a three-dimensional model, considering the two-phase model. The primary objective of this study is to transform the governing equations of the flow model into a set of ordinary differential equations by employing the three-parameters group technique. Based on the innovative discoveries, two models incorporating new associated functions have been successfully developed for two distinct scenarios characterized by the power-law index, n. The impact of physical factors on the velocity profile, temperature distribution, concentration field, and entropy output of the system is clearly illustrated through a variety of graphs. The results indicated that the inclination angle of 20 degrees had the best thermal characteristics compared to other inclinations. The entropy generation reached its maximum value at temperature difference of 13 K due to irreversibility of the system, which indicates that the system is more efficient. Furthermore, the increasing percentage in Nusselt number is predicted to be 28.18% when the Prandtl number is taken a range (4 ≤ 𝑃𝑟 ≤ 6). The Sherwood number enhanced up to 18.61% with a range (0.1 ≤ 𝑁 𝑏 ≤ 0.5) of Brownian motion. A quantitative comparison is conducted between the present results and the literature in order to validate the superior efficiency of the used method.